2022
DOI: 10.1021/acsomega.2c01969
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptobenzimidazole-Based 1,3-Thaizolidin-4-ones as Antidiabetic Agents: Synthesis, In Vitro α-Glucosidase Inhibition Activity, and Molecular Docking Studies

Abstract: In this research work, we have focused our efforts to synthesize a series of 2-mercaptobenzimidazole-based 1,3-thiazolidin-4-ones ( 5–24 ) following a multistep reaction strategy and characterization of the synthesized derivatives with the help of various spectroscopic techniques. To find the antidiabetic potentials of the synthesized compounds ( 5–24 ), in vitro alpha-glucosidase inhibitory activity was performed using acarbose (IC 50 = 873 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Figure 4(B) shows the results of the Ramachandran plot for the ⊍-glucosidase protein obtained from homology modeling. 45 Supporting Information Table S1 summarizes the molecular docking energy scoring of the EGC and EGCG compounds with the ⊍-glucosidase protein and the predicted inhibitory activity values (K i ). The experimental binding energies obtained through calculation and the theoretical docking binding energies obtained through molecular docking are presented in Table 1 and Table S1, respectively.…”
Section: Docking Analysismentioning
confidence: 99%
“…Figure 4(B) shows the results of the Ramachandran plot for the ⊍-glucosidase protein obtained from homology modeling. 45 Supporting Information Table S1 summarizes the molecular docking energy scoring of the EGC and EGCG compounds with the ⊍-glucosidase protein and the predicted inhibitory activity values (K i ). The experimental binding energies obtained through calculation and the theoretical docking binding energies obtained through molecular docking are presented in Table 1 and Table S1, respectively.…”
Section: Docking Analysismentioning
confidence: 99%
“…Synthesis of mercaptobenzimidazole‐Based 1,3‐Thaizolidin‐4‐ones derivatives 30 and antidiabetic evaluation via alpha‐glucosidase inhibitory assay have been reported by Khan et al. [51] . Among the synthesized compounds 30 a displayed the highest degree of inhibition against alpha‐glucosidase enzyme with an IC 50 value of 5.22 μM which was 167‐fold more active than the standard acarbose which displayed an IC 50 value of 873 μM (Figure 30), respectively.…”
Section: Biological Activities Of Thiazolidinone Containing Heterocyclesmentioning
confidence: 84%
“…Synthesis of mercaptobenzimidazole-Based 1,3-Thaizolidin-4-ones derivatives 30 and antidiabetic evaluation via alphaglucosidase inhibitory assay have been reported by Khan et al. [51] Among the synthesized compounds 30 a displayed the highest degree of inhibition against alpha-glucosidase enzyme with an IC 50 value of 5.22 μM which was 167-fold more active than the standard acarbose which displayed an IC 50 value of 873 μM (Figure 30), respectively. Moreover, molecular docking in the active gorge of homology-modelled alpha-glucosidase revealed that compound 30 a formed various interactions with various active site amino acid residues which could explain the observed activity.…”
Section: Thiazolidinone-benzimidazole Hybridsmentioning
confidence: 89%
“…A crucial strategy for avoiding type II diabetes mellitus' deadly effects is to control blood glucose levels. Hence, there is an immense need to synthesize new small molecules and to evaluate their anti-diabetic potential against α-glucosidase, might be used as drug candidates for the treatment of type II diabetes mellitus [5][6][7][8][9] . Several therapeutic approaches of diabetes are available,…”
mentioning
confidence: 99%
“…The docking results of compounds 3a-3y.CH 3 ), 3.74 (s,3H, CH 3 ), 6.77-6.82 (m,2H),6.86(d,1H, J = 7.8 Hz),6.89(d,1H, J = 10.2 Hz), 6.97(d,1H, J = 7.8 Hz), 7.02(t,1H, J = 7.8 Hz), 7.04-7.07 (m,2H), 7.23-7.26 (m,2H), 7.63(s,1H),7.79(s,1H), 8.31(d,1H, J = 7.8 Hz),8.46(s, 1H),13.051(s,1H); 13 C-NMR δppm; 21.74, 55.7, 114.7, 116.9, 118.6, 119.0, 119.3, 120.3, 120.6, 122.8, 123.9, 127.9, 128.7, 133.0, 138.1, 138.4, 138.8, 148.0, 150.2, 152.8, 164.2; C 22 H 21 N 3 O 3 (375.43) m/z (%): 376.16[M + H] + (100). Hz), 7.31 (d,2H, J = 7.8 Hz), 7.49 (d,3H, J = 7.2 Hz), 7.70 (d,1H, J = 7.2 Hz), 8.22 (d,1H, J = 8.4 Hz),8.46(s,1H),8.60 (s,1H),9.74 (s,1H), 9.80(s,1H); 13 C-NMR ppm; 55.8,111.8, 115.5,117.1,118.3,119.7,122.0, 124.5, 126.4,127.9,128.7, 134.1,138.7,138.8,148.0,150.6,152.1,159.6; C 21 H 18 ClN 3 O 3 (395.84) m/z (%): 396.10[M + H] + (100).…”
mentioning
confidence: 99%